cfDNA and DNases: new biomarkers of sepsis in preterm neonates$da pilot study - Lenz, Moritz; Maiberger, Thomas; Armbrust, Lina; Kiwit, Antonia; Von der Wense, Axel; Reinshagen, Konrad; Elrod, Julia; Boettcher, Michael (Cells, 2022)
Introduction: An early and accurate diagnosis of early onset neonatal sepsis (EONS) and late onset neonatal sepsis (LONS) is essential to improve the outcome of this devastating conditions. Especially, preterm infants are at risk. Reliable biomarkers are rare, clinical decision-making depends on clinical appearance and multiple laboratory findings. Markers of NET formation and NET turnover might improve diagnostic precision. Aim of this study was to evaluate the diagnostic value of NETs in sepsis diagnosis in neonatal preterm infants. Methods: Plasma samples of neonatal preterm infants with suspected sepsis were collected. Blood samples were assayed for markers of NET formation and NET turnover: cfDNA, DNase1, nucleosome, NE, and H3Cit. All clinical findings, values of laboratory markers, and epidemiological characteristics were collected retrospectively. Two subpopulations were created to divide EONS from LONS. EMA sepsis criteria for neonatal sepsis were used to generate a sepsis group (EMA positive) and a control group (EMA negative). Results: A total of 31 preterm neonates with suspected sepsis were included. Out of these, nine patients met the criteria for sepsis according to EMA. Regarding early onset neonatal sepsis (3 EONS vs. 10 controls), cfDNA, DNase I, nucleosome, and CRP were elevated significantly. H3Cit and NE did not show any significant elevations. In the late onset sepsis collective (6 LONS vs. 12 controls), cfDNA, DNase I, and CRP differed significantly compared to control group.
Gesehen am 03.05.2023